(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Based on the Journal Citation Reports that the common method of suicide was drug overdose in 62% of the cases, hanging in 31% and jumping in 8% and also 30% suicide succeeded the attempted at end of one year, two-thirds of the suicides occurred at least 15 years after the suicide attempts. The nurse should be handling the psychiatric patient carefully.